LAYANAN DALAM BIMBINGAN DAN KONSELING BAGI PESERTA DIDIK DI SEKOLAH - Eva Sasmita; Miftah Rahmadini; Fakhrur Razi; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Guidance and counseling are very important in education to help students find solutions to the problems they face and develop their potential. This service also aims to shape students' character and encourage independence. Implementation of these services should focus on individual needs and problems for maximum effectiveness. This research uses a literature study method to explain guidance and counseling services in schools, which have the mission of supporting each individual to achieve maximum potential according to their personal needs and uniqueness. Factors such as talent, family, education, economy and environment are also considered so that individual development is positive.